Activation of the Alternative Pathway of Complement is a Feature of Preterm Parturition but Not of Spontaneous Labor at Term - Vaisbuch, Edi (2010)
PROBLEM: Plasma concentrations of fragment Bb (FBb) are a marker for activation of the alternative pathway of the complement system. High concentrations of FBb in maternal blood, as early as the first trimester, are associated with subsequent spontaneous preterm delivery <34 weeks of gestation. The study aim was to determine whether spontaneous preterm labor with intact membranes (PTL), intra-amniotic infection/inflammation (IAI) or labor at term are associated with alterations in circulating maternal FBb concentrations. METHOD OF STUDY: This cross-sectional study included women in the following groups: 1) non-pregnant (n=40); 2) normal pregnancy (gestational age range 20-36 6/7 weeks, n=63); 2) women at term not in labor (n=70); 3) women at term in spontaneous labor (n=59); 4) patients with an episode of PTL who delivered at term (n=62); 5) PTL without IAI who delivered preterm (n=30); and 6) PTL with IAI who delivered preterm (n=67). Maternal plasma FBb concentrations were determined by ELISA. RESULTS: 1) Among patients with PTL, those who had a preterm delivery either with IAI (1.21 μg/ml, IQR 0.77-2.16) or without IAI (1.13 μg/ml, IQR 0.92-2.08;) had a higher median maternal plasma FBb concentration than those who delivered at term (0.86 μg/ml, IQR 0.64-1.57; p=0.007 and p=0.026, respectively); 2) there was no difference in the median plasma FBb concentration between patients with and without IAI who delivered preterm (p=0.9); 3) in contrast, spontaneous labor at term was not associated with a significant change in the maternal plasma FBb concentration (p=0.8); 4) maternal plasma concentration of FBb did not differ significantly between normal pregnant women and the non-pregnant controls (p=0.8) and were not correlated with advancing gestational age (r −0.28, p=0.8). CONCLUSIONS: 1) Preterm parturition is associated with activation of the alternative complement pathway in maternal circulation; 2) such activation is not detectable in spontaneous labor at term; 3) intra-amniotic infection/inflammation does not explain the activation of the alternative pathway of complement in preterm labor. Collectively, these observations suggest that preterm and term labor have fundamental differences in the regulation of innate immunity.